Integrative Biomimetics of Autonomous Hexapedal Locomotion - Dürr, Volker; Arena, Paolo P.; Cruse, Holk; Dallmann, Chris J.; Drimus, Alin; Hoinville, Thierry; Krause, Tammo; Mátéfi-Tempfli, Stefan; Paskarbeit, Jan; Patanè, Luca; Schäffersmann, Mattias; Schilling, Malte; et al. (Frontiers in Neurorobotics, 2019)
Despite substantial advances in many different fields of neurorobotics in general, and biomimetic robots in particular, a key challenge is the integration of concepts: to collate and combine research on disparate and conceptually disjunct research areas in the neurosciences and engineering sciences. We claim that the development of suitable robotic integration platforms is of particular relevance to make such integration of concepts work in practice. Here we provide an example for a hexapod robotic integration platform for autonomous locomotion. In a sequence of six focus sections dealing with aspects of intelligent, embodied motor control in insects and multipedal robots - ranging from compliant actuation, distributed proprioception and control of multiple legs, the formation of internal representations to the use of an internal body model - we introduce the walking robot HECTOR as a research platform for integrative biomimetics of hexapedal locomotion. Owing to its 18 highly sensorised, compliant actuators, light-weight exoskeleton, distributed and expandable hardware architecture, and an appropriate dynamic simulation framework, HECTOR offers many opportunities to integrate research effort across biomimetics research on actuation, sensory-motor feedback, inter-leg coordination, and cognitive abilities such as motion planning and learning of its own body size.